THE SILENT GRIEVANCES AND UNTOLD REGRETS: Cultural Reconciliation of the Nahdliyyin and the Former 1965 Political Prisoners in South Blitar (JOURNAL OF INDONESIAN ISLAM, 2025)
Between 1965 and 1968, South Blitar as the “last defense” of Indonesian Communist Party (PKI) underwent military operation. In East Javanese’s memories, PKI members frequently clashed with members of Nahdlatul Ulama (NU), Indonesia’s largest Muslim organization prior to the 1965 coup, and led to thousands of deaths, mostly among PKI affiliates afterwards. For decades, both groups lived in silent grievance. From the mid-1980s, under NU leader Abdurrahman Wahid (Gus Dur), a new movement toward understanding and reconciliation emerged. This research examines how Syarikat, an informal NU youth network inspired by Gus Dur’s vision, facilitated cultural reconciliation in South Blitar without relying on formal NU structures. Based on oral histories and narrative analysis (2021–2024), the study highlights the role of religious legitimacy and moral authority in reshaping perceptions and building trust. The findings suggest that culturally grounded, empathetic dialogue rooted in shared spiritual values can heal historical divisions and promote social inclusion.